Adaptation of the Classroom Cultural Diversity Climate Scale for Russia - Khairutdinova, Rezeda R.; Gromova, Chulpan R.; Zheltukhina, Marina R.; Chistyakov, Alexey A.; Daitgadzhiev, Gamadali M. (Journal of Ethnic and Cultural Studies, 2022)
School climate is an underestimated factor for sustainable development and resilience in the educational context. There is a need to develop and implement specific prevention and intervention programs that help maintain a positive school climate in cultural diversity to ensure psychological well-being, successful adjustment, academic achievement, integration of students from diverse cultural backgrounds, and prevention of extremism among youth. The current study tested the Classroom Cultural Diversity Climate Scale (CCDCS) in the context of cultural diversity in Russian schools. Participants included students with and without an immigrant background. Russian students had difficulty answering questions about racism and discrimination because these topics are not covered in the secondary school curriculum. The research results showed that the questionnaire questions effectively provided an impetus to test further the validity and reliability of the CCDCS for Russian participants. The adapted questionnaire will make it possible to examine the descriptive norms of school policies related to diversity. In addition, the questionnaire can be used to identify factors that influence the learning efficiency and adjustment of students from diverse cultural backgrounds, including immigrant students.